Overcoming oncogene addiction in breast and prostate cancers: a comparative mechanistic overview. Issue 2 (February 2021) - Blatt, Eliot B; Kopplin, Noa; Kumar, Shourya; Mu, Ping; Conzen, Suzanne D; Raj, Ganesh V
Abstract : Prostate cancer (PCa) and breast cancer (BCa) are both hormone-dependent cancers that require the androgen receptor (AR) and estrogen receptor (ER, ESR1) for growth and proliferation, respectively. Endocrine therapies that target these nuclear receptors (NRs) provide significant clinical benefit for metastatic patients. However, these therapeutic strategies are seldom curative and therapy resistance is prevalent. Because the vast majority of therapy-resistant PCa and BCa remain dependent on the augmented activity of their primary NR driver, common mechanisms of resistance involve enhanced NR signaling through overexpression, mutation, or alternative splicing of the receptor, coregulator alterations, and increased intracrine hormonal synthesis. In addition, a significant subset of endocrine therapy-resistant tumors become independent of their primary NR and switch to alternative NR or transcriptional drivers. While these hormone-dependent cancers generally employ similar mechanisms of endocrine therapy resistance, distinct differences between the two tumor types have been observed. In this review, we compare and contrast the most frequent mechanisms of antiandrogen and antiestrogen resistance, and provide potential therapeutic strategies for targeting both advanced PCa and BCa.